Research on smoke diffusion and evacuation routes of mine fires with complex roadway networks - Menghui Xiao; Cuifeng Du; Yuan Wang; Jiuzhu Wang; Baomeng Chang (Case Studies in Thermal Engineering)
It is meaningful to study the diffusion of toxic substances and evacuation routes in metal mine fires. In this paper, numerical simulation was employed to investigate the characteristics of smoke diffusion, the variations in fire-induced pressure, and the evacuation routes of miners in full-scale mine fire scenarios. The results indicated that CO concentration significantly decreased at roadway corners, and both CO concentration and temperature gradually decreased with increasing depth. It is a good choice for miners to escape towards the deeper areas or along curved structural directions. Miners in the working face near the fire zone had an optimal evacuation window of only 3 min, and the optimal evacuation times varied for different mining levels and sublevels. Consequently, miners must formulate different evacuation plans within the optimal time frame. The fire-induced pressure is exponentially related to temperature rise, with a fitted equation for a 10° ramp expressed as Pfire = 150.58ΔT0.18. A methodology for planning mine fire evacuation routes was proposed, resulting in improved evacuation routes that allow miners to avoid more dangerous routes, thereby significantly enhancing evacuation safety.